Kontribusi Islamic Worldview di Era Kontemporer Kajian dari Fungsinya - Sumiran, Sumiran; Pambudi, Riski Kristianto; Al Ithriy, Abu Husein Ibrahim; Priyanto, Priyanto (Lembaga Yasin AlSys, 2026)
Islam, as a religion grounded in divine revelation, offers a comprehensive and integrated worldview known as the Islamic Worldview, which plays a strategic role as the foundation for thought and action among Muslims. The Islamic Worldview functions as a guide for filtering diverse emerging values and as a basis for constructing educational, social, economic, and scientific systems oriented toward public benefit (maslahah) and justice. In light of this need, examining the function of the Islamic Worldview becomes essential to contributing to the formation of appropriate and just patterns of thought and attitude in order to achieve collective well-being. This study employed a library research method by collecting, organizing, and analyzing relevant sources in the form of articles, books, and previous research. The findings show that the Islamic Worldview has a significant role in responding to contemporary challenges, including serving as a foundation for strengthening aqidah; as a source of moral and ethical values derived from revelation; as guidance in determining life goals; as a bulwark against external influences such as liberalism, secularism, and materialism; and as a basis for social and scientific action that integrates orientations toward both worldly life and the hereafter. These findings affirm that strengthening the Islamic Worldview is crucial in shaping the framework of thought, attitudes, and behavior of Muslims that are just and oriented toward the attainment of the common good.